Wasatiyyah : pemacu peradaban negara - Seminar Wasatiyyah Pemacu Peradaban Negara (2013 : Kuala Lumpur, Malaysia); Murshaddad Hasbullah; Mohd. Asri Abdullah; Institut Wasatiyyah Malaysia (Putrajaya, Malaysia : Institut Wasatiyyah Malaysia, Jabatan Perdana Menteri, 2013)
On wasatiyyah, a moderation aspects in Islam practiced in Malaysia; papers of a seminar.
Koleksi Sumbangan : Abdul Ghafar Ibrahim (AGI)
Includes bibliographical references.
In Malay.
Keywords: Moderation -- Religious aspects -- Islam -- Congresses; Moderation -- Social aspects -- Malaysia -- Congresses